Reappraisal of the Principles Influential in the Theory of Relation Change - ?????, ???? (??? ? ????)
There are five legal (uṣūlī) issues posited in legal theorists’ (uṣūlīs) statements as principles effective in theory of the relation change (inqilāb-i nisbat = change of relation between two conflicting reasons in the face of the third). The claim brought up about the issues in question is that the kind of principle accepted in any issue is effective in acceptance or rejection of the theory of relation change. In the author’s opinion, two issues from among the claimed instances are effective in systematization of the theory of relation change and not of the main theory; and the other three theories can, on any basis in which they are adopted, accept the theory of relation change and the kind of basis adopted in those issues have no effect on rejecting the theory of relation change. Therefore, the basic objections made in the legal theorists’ statements on this theory are incomplete.